Minimizing Misalignment and Frame Protrusion of Shoulder Exoskeleton via Optimization for Reducing Interaction Force and Minimizing Volume - Jihwan Yoon; Sumin Kim; Junyoung Moon; Jehyeok Kim; Giuk Lee (Machines, 2022)
Although industrial shoulder exoskeletons have undergone rapid advancement, their acceptance by industrial workers is limited owing to the misalignment and interference between the exoskeletal frame and the wearer’s body and bulkiness of the frames. Several joint mechanisms have been developed to offset misalignments; however, none of the existing systems can simultaneously alleviate the interference and bulkiness problems. Furthermore, the reduction in the misalignments in terms of forces generated at the human–robot interface has not been experimentally verified. Therefore, in this study, design optimization was performed to address the various factors that limit the use of the existing industrial shoulder exoskeletons. Upper body motions were captured and converted into a target trajectory for the exoskeleton to follow. The optimal prismatic–revolute–revolute joint configuration was derived and used to manufacture a skeletal mock-up, which was used to perform experiments. The misalignments of the optimized configuration in the considered motions were 67% lower than those for the conventional joint configuration. Furthermore, the interaction forces were negligible (1.35 N), with a maximum reduction of 61.8% compared to those of conventional configurations.